2015
DOI: 10.1007/s12032-015-0578-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase I pilot study of the insulin-like growth factor 1 receptor pathway modulator AXL1717 in combination with gemcitabine HCl and carboplatin in previously untreated, locally advanced, or metastatic non-small cell lung cancer

Abstract: AXL1717 is an orally bioavailable IGF-1R pathway modulator that has been shown to have anti-tumoral effects. The objectives of the present study were to define maximum tolerated dose and the recommended phase II dose (RPTD) of AXL1717 in combination with gemcitabine HCl and carboplatin in non-small cell lung cancer (NSCLC). Patients with previously untreated, locally advanced, or metastatic NSCLC (squamous cell cancer or adenocarcinoma) in good performance status and with preserved major organ functions were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The practical feasibility of combination ALK/IGF-1R inhibition as a clinical strategy has been given a boost by recent research into the IGF-1R inhibitor AXL1717 in advanced non-small cell lung cancer. Early results have indicated that as a monotherapy AX1717 is as effective as existing chemotherapy and with less toxicity 22 24 . Moreover, the role of IGF-1R activation in non-small lung cancer prognosis has been very recently confirmed in a study of 326 NSCLC patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The practical feasibility of combination ALK/IGF-1R inhibition as a clinical strategy has been given a boost by recent research into the IGF-1R inhibitor AXL1717 in advanced non-small cell lung cancer. Early results have indicated that as a monotherapy AX1717 is as effective as existing chemotherapy and with less toxicity 22 24 . Moreover, the role of IGF-1R activation in non-small lung cancer prognosis has been very recently confirmed in a study of 326 NSCLC patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be effective in inhibiting various types of cancers including those of the gastrointestinal tract, nasopharynx, liver, lung, ovary, soft tissues, and hematopoietic system including NPM-ALK + T cell lymphoma [21, 3446]. Recently, however, higher doses of PPP have been shown to induce bone marrow toxicity in some patients [30]. In this paper, we tested the hypothesis that dual suppression of ALK and IGF-IR could represent a superior strategy that significantly improves the effects of the isolated inhibition of each enzyme alone.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, small molecule IGF1R inhibitors-as well as inhibitors of other components of the IGF1R pathway-may still hold clinical potential when used in combination therapies. For example, combination of AXL1717 (picropodophyllin), an IGF1R pathway inhibitor, with gemcitabine HCl and carboplatin yielded an acceptable toxicity profile in previously untreated, locally advanced, or metastatic NSCLC (Holgersson et al, 2015). Similarly, BMS-754807 is a reversible small molecule inhibitor of IGF1R and insulin receptor (IR) (Carboni et al, 2009) that has demonstrated effectiveness in vitro in combination with anti-cancer therapies for the treatments of breast, pancreatic, colon, lung, and gastric cancers (Carboni et al, 2009).…”
Section: Pharmacological Autophagy Modulation As An Approach To Cancementioning
confidence: 99%